Research on Development Status and Implementation Path of Wind-Solar-Water-Thermal-Energy Storage Multi-Energy Complementary Demonstration Project - KANG Junjie; ZHAO Chunyang; ZHOU Guopeng; ZHAO Liang (发电技术)
The multi-energy complementary demonstra-tion projects of wind-solar-water-thermal-energy storage focuses on the development from the power side, and forms a complementary operation mode by using wind energy, solar energy, hydropower, coal to generate electricity. Multi-energy complementarity can effectively solve the problems of wind abandoning, light abandoning, water abandoning and power limiting, promote the absorption of renewable energy nearby, realize the stable delivery of electricity and improve the comprehensive utilization efficiency of energy. This paper summarized the connotation construction principles of multi-energy complementarity, detailed the development status and existing problems of the first batch of multi-energy complementarity demonstration projects, and analyzed in detail the development paths of different modes of multi-energy complementarity projects. This paper focused on the evaluation of wind and solar resources, new energy site planning, total installed capacity and optimal power ratio, optimal allocation of energy storage, coordinated control technology to ensure safety and stability and economic evaluation indicators of the project, so as to extract the general process and development mode suitable for the construction and promotion of multi-energy complementary projects. Finally, some summary and suggestions were put forward from the aspects of top-level design, market mechanism and operation management.